Direct anticoagulant drugs to overcome limitations of vitamin K antagonists. A critical appraisal of data in atrial fibrillation patients. (March 2013) - Di Minno, Matteo Nicola Dario; Russolillo, Anna; Di Minno, Alessandro; Camera, Marina; Parolari, Alessandro; Tremoli, Elena
<x xml:space="preserve">Abstract</x> Introduction: The usefulness of anticoagulation in patients with atrial fibrillation (AF) is well known. However, the inherent limitations of vitamin K antagonists (VKAs) have made the development of new oral anticoagulants necessary. Drugs directed against thrombin or the factor Xa are currently available. Areas covered: These molecules, being administered at fixed doses and not requiring laboratory monitoring, overcome one crucial problem associated with the use of VKAs. However, data about the bleeding risk related to the use of these molecules should be further analyzed. Expert opinion: The efficacy of direct anticoagulants (DACs) in AF-related stroke prevention has been considered the primary outcome in all Phase III published trials. On the other hand, the reduction of the bleeding risk is an important goal achieved by the DACs as compared with VKAs. Besides data deriving from randomized trials, when talking about new drugs, the need of evidences from the 'everyday clinical practice' are often requested. The aim of this literature revision is to report and analyze data from specific subgroups about which little is known. In particular, information about the use of DACs in oncologic patients, in patients receiving concomitant antiplatelet drugs and in the perioperative period is currently lacking. The parallel evaluation of all these data may lead to the identification of clinical and demographical criteria to choose when to switch to DACs.